MERAWAT TOLERANSI DI RUANG VIRTUAL: DAKWAH ISLAM MODERAT SEBAGAI STRATEGI KONTRA-RADIKALISME - Gelah Aramiko; Riyandi S; Zulfan Fahmi (AT-TAWASUL, 2024)
The digital era brings new opportunities and challenges for the world of da'wah. Social media has become a strategic space for shaping public opinion, including in spreading religious values. However, the proliferation of radical and intolerant religious content in virtual spaces poses a serious threat to social harmony. This article analyses how moderate Islamic da'wah can be used as a narrative strategy to nurture tolerance and prevent the spread of digital-based radicalism. This study employs a qualitative-descriptive approach using literature review methods. The findings indicate that moderate Islamic da'wah, which emphasises the values of moderation, tolerance, and interfaith dialogue, plays a crucial role in balancing religious narratives on social media and countering the infiltration of radical ideologies.